Overcoming the dichotomy between nature and culture for the management of the natural heritage in the city: the multiple representations of the Dois Irmãos Forest, Recife – PE - Moura, Célio Henrique Rocha; Bezerra, Onilda Gomes; Lapa, Tomás de Albuquerque; Mota, Maiara Costa (Revista Nacional de Gerenciamento de Cidades, 2022)
This article discusses the issue of heritage management of Atlantic Forest fragments in Brazil, especially in the city of Recife. As ecosystems in urban territory, established as Protected Units, the forest remnants are carriers of socio-cultural meanings, recognized by the natural and cultural values they evoke. The empirical object investigated is the Nature Conservation Unit Mata de Dois Irmãos, which was analyzed as a heritage asset focusing not only on natural processes, but especially on human processes apprehended from the interrelationship established with the site, directly or indirectly. The observation was mediated by semi-structured interviews, listening to local agents (residents), as well as specialists and public managers who are somehow involved with this heritage site. From the analysis, it was possible to apprehend representations that translate the values that are attributed to the ecosystem in question. The results obtained showed the essence contained in the intertwining between the natural and cultural dimensions, interpreted from the expressions and attitudes exposed by those who interact with the urban environment in which it is inserted and with which it relates, which gives relevance to the sociocultural dimension in the existence and permanence of ecosystems, and should be taken into account in the operational process of conservation management of the natural heritage in the city.